2018
DOI: 10.1186/s13660-018-1935-0
|View full text |Cite
|
Sign up to set email alerts
|

A tensor trust-region model for nonlinear system

Abstract: It has turned out that the tensor expansion model has better approximation to the objective function than models of the normal second Taylor expansion. This paper conducts a study of the tensor model for nonlinear equations and it includes the following: (i) a three dimensional symmetric tensor trust-region subproblem model of the nonlinear equations is presented; (ii) the three dimensional symmetric tensor is replaced by interpolating function and gradient values from the most recent past iterate, which avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Let us first consider the case in which the Taylor model is employed. It follows from (31), (24) and ( 29) that for all…”
Section: Local Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…Let us first consider the case in which the Taylor model is employed. It follows from (31), (24) and ( 29) that for all…”
Section: Local Convergencementioning
confidence: 99%
“…In recent publications also methods of higher order start to gain interest, see for example [2,24]. In [2] in particular, it has been observed that the good complexity bound of ARC can be made even lower, if one is willing to use higher-order derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In recent publications also methods of higher order start to gain interest, see for example [6,41]. In [6] in particular, it has been observed that the good complexity bound of ARC can be made even lower, if one is willing to use higher-order derivatives.…”
mentioning
confidence: 99%